2016 Index IEEE Transactions on Consumer Electronics volume 62 [Author Index] (IEEE transactions on consumer electronics, 2016)
This index covers all technical items—papers, correspondence, reviews, etc.—that appeared in this periodical during 2016, and items from previous years that were commented upon or corrected in 2016. Other items may also be covered if they have been judged to have archival value. The Author Index contains an entry for each paper. The entry includes the title of the paper or other item, and its location, specified by the publication abbreviation, year, month, and inclusive pagination. The Subject Index contains entries describing the item under all appropriate subject headings, plus the first author's name, the publication abbreviation, month, and year, and inclusive pages. Subject cross-references are included to assist in finding items of interest.